2023
DOI: 10.1002/smll.202300744
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Approaches for Prevention and Treatment of Chemotherapy‐Induced Neurotoxicity, Neuropathy, and Cardiomyopathy in Breast and Ovarian Cancer Survivors

Abstract: Nanotechnology has emerged as a promising approach for the targeted delivery of therapeutic agents while improving their efficacy and safety. As a result, nanomaterial development for the selective targeting of cancers, with the possibility of treating off‐target, detrimental sequelae caused by chemotherapy, is an important area of research. Breast and ovarian cancer are among the most common cancer types in women, and chemotherapy is an essential treatment modality for these diseases. However, chemotherapy‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 285 publications
0
3
0
Order By: Relevance
“…Meanwhile, the presence and remission of ascites in this patient were closely related to the treatment, thus indicating that ascites may be an adverse effect of the anti-tumor therapy. Adverse reactions of chemotherapy mainly include adverse reactions at the injection site (phlebitis), digestive system adverse reactions (nausea and vomiting), bone marrow suppression, organ function damage (toxicity of heart, liver, and kidney), neurotoxicity, hair loss, and skin reactions while the adverse effects of monoclonal antibodytargeted therapy are hypersensitive reaction, arterial and venous thromboembolic events, diarrhea, nausea, vomiting, and so on (16)(17)(18). As for anti-Claudin18.2 antibody therapy, the most common adverse effects are vomiting and nausea (19).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the presence and remission of ascites in this patient were closely related to the treatment, thus indicating that ascites may be an adverse effect of the anti-tumor therapy. Adverse reactions of chemotherapy mainly include adverse reactions at the injection site (phlebitis), digestive system adverse reactions (nausea and vomiting), bone marrow suppression, organ function damage (toxicity of heart, liver, and kidney), neurotoxicity, hair loss, and skin reactions while the adverse effects of monoclonal antibodytargeted therapy are hypersensitive reaction, arterial and venous thromboembolic events, diarrhea, nausea, vomiting, and so on (16)(17)(18). As for anti-Claudin18.2 antibody therapy, the most common adverse effects are vomiting and nausea (19).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, immunotherapy represents a change in paradigm in cancer therapy since, in this case, the antineoplastic agents, instead of directly contrasting cancer cells, have the potential to activate the patient’s immune system to become able to attack cancer cells powerfully and successfully. However, it should be underlined that the drawbacks existing for the conventional therapeutic approaches, such as low response rate, dangerous side effects, development of resistance, immunosuppression, and high recurrence rate chemotherapy, are also reported for the most innovative therapeutic strategies, and new routes are being investigated to overcome these problems [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is the main modality for tumor treatment . However, conventional chemotherapeutic drugs have problems, such as unsatisfactory effects and insufficient accumulation. In recent years, nanocarriers have received increasing attention due to their excellent properties as drug delivery systems. , With the deepening of research, studies have shown that the nanoparticle size is closely linked to its penetration and accumulation abilities. Small nanoparticles easily penetrate deep into tumor tissues, but they can also be readily cleared, resulting in insufficient accumulation.…”
Section: Introductionmentioning
confidence: 99%